2016
DOI: 10.1002/term.2206
|View full text |Cite
|
Sign up to set email alerts
|

Development of a wearable bioartificial kidney using the Bioartificial Renal Epithelial Cell System (BRECS)

Abstract: Cell therapy for the treatment of renal failure in the acute setting has proved successful, with therapeutic impact, yet development of a sustainable, portable bioartificial kidney for treatment of chronic renal failure has yet to be realized. Challenges in maintaining an anticoagulated blood circuit, the typical platform for solute clearance and support of the biological components, have posed a major hurdle in advancement of this technology. This group has developed a Bioartificial Renal Epithelial Cell Syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…These devices include an extracorporeal cellular unit of renal proximal tubule epithelial cells, which express multiple transporters that cooperate in basolateral uptake and luminal excretion of various endogenous metabolites, including uremic toxins . FDA‐approved phase I/II clinical studies with a RAD suggested a potential added value of such a device in the treatment of critically ill subjects . The development, current status, and technical challenges of RADs have been extensively reviewed elsewhere .…”
Section: Introductionmentioning
confidence: 99%
“…These devices include an extracorporeal cellular unit of renal proximal tubule epithelial cells, which express multiple transporters that cooperate in basolateral uptake and luminal excretion of various endogenous metabolites, including uremic toxins . FDA‐approved phase I/II clinical studies with a RAD suggested a potential added value of such a device in the treatment of critically ill subjects . The development, current status, and technical challenges of RADs have been extensively reviewed elsewhere .…”
Section: Introductionmentioning
confidence: 99%
“…To try to overcome these problems, the same research group developed a Bioartificial Renal Epithelial Cell System (BRECS) [57,58]. The BRECS technology, based on niobium-coated carbon and cryopreservable polycarbonate seeded with human renal tubular epithelial cells derived from adult progenitor cells, recently demonstrated efficacy when applied in series to a hemofilter in a porcine septic shock model [59] and as a wearable device connected to a peritoneal dialysis circuit in an anephric sheep model [60]. Although promising, the BRECS technology is yet to be applied in clinical trials.…”
Section: Bioartificial Kidneymentioning
confidence: 99%
“…One way to achieve this goal is to expand the functionality of conventional therapies by including cellular components capable of taking over tubular functions of the kidney, thus introducing the critical transport, metabolic, and endocrine functions of the kidney (Figure 2) [ [12][13][14]. In recent years, substantial progress has been made in the development of the BAK (Table 3) [61][62][63][64][65][66][67]. Because of the targeted high capacity clearance of PBUT, this approach is expected to result in considerable lowering of PBUT plasma concentrations [68], which may significantly reduce (cardiovascular) morbidity and mortality and increase quality of life [69].…”
Section: The Bioartificial Kidney: Approaching the Clinicsmentioning
confidence: 99%
“…Thus, elimination of a blood circuit, an inherent characteristic of HD-based therapy, would facilitate its development. One approach being explored is a wearable bioartificial kidney (WeBAK) for PD, a type of BRECS that uses peritoneal dialysate to provide oxygen and nutrients to the cells [67]. For uremic control sorbent technology is applied to regenerate the peritoneal dialysate, which is subsequently perfused through the BRECS, providing tubular cell functions [67].…”
Section: The Wearable Bak: An Update On the Bioartificial Renal Epithmentioning
confidence: 99%